2011
DOI: 10.1038/npp.2011.99
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Neurobiological Phenotypes Associated with Alcohol Use Disorder Severity

Abstract: Although numerous studies provide general support for the importance of genetic factors in the risk for alcohol use disorders (AUDs), candidate gene and genome-wide studies have yet to identify a set of genetic variations that explain a significant portion of the variance in AUDs. One reason is that alcohol-related phenotypes used in genetic studies are typically based on highly heterogeneous diagnostic categories. Therefore, identifying neurobiological phenotypes related to neuroadaptations that drive the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
203
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(231 citation statements)
references
References 85 publications
(92 reference statements)
18
203
4
1
Order By: Relevance
“…One investigates brain response to alcohol stimuli. Treatment-naive subjects with a minimum of fi ve heavy drinking episodes in the past month were recruited through advertisements (Claus et al, 2011a). Heavy episodic drinking was defi ned as fi ve or more drinks per episode for men and four or more drinks for women.…”
Section: Subjects and Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…One investigates brain response to alcohol stimuli. Treatment-naive subjects with a minimum of fi ve heavy drinking episodes in the past month were recruited through advertisements (Claus et al, 2011a). Heavy episodic drinking was defi ned as fi ve or more drinks per episode for men and four or more drinks for women.…”
Section: Subjects and Tasksmentioning
confidence: 99%
“…Repeated fi ndings have shown signifi cant activation in the striatum, medial frontal, insula, and anterior cingulate regions (Filbey et al, 2008;George et al, 2001;Tapert et al, 2004;Wrase et al, 2002) during exposure to alcohol cues. These types of cue exposure studies have also characterized the alcohol-craving responses in connection with alcohol-dependence severity (Claus et al, 2011a;Filbey et al, 2008). Similarly, there have been many investigations of brain responses to smoking cues, showing increased activation in the orbitofrontal cortex, anterior cingulate, striatum, nucleus accumbens, and ventral tegmental area (David et al, 2005;Franklin et al, 2011;Lee et al, 2005;Lim et al, 2005), in which responses were also analyzed for associations with various clinical assessments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these interpretations, correlations between alcohol cue-elicited activation of the precuneus and alcohol craving (Park et al, 2007;Tapert et al, 2003), as well as a variety of measures of alcohol use disorder severity, including Alcohol Use Disorders Identifi cation Test score and years of heavy drinking (Claus et al, 2011), have been reported. A recent study investigating the relationship of genome-wide copy number variations with alcohol cue-elicited activation in participants with alcohol use disorders found that the precuneus mediated the association between the homozygous deletions at copy number variation region 22q13.1 and alcohol dependence severity.…”
Section: Discussionmentioning
confidence: 48%
“…Earlier studies in individuals with alcohol use disorders have implicated the striatum, amygdala and MPFC in reward processing and have linked activation in these areas to craving and approach behaviour. [7][8][9][10][11][12][15][16][17]43 However, to our knowledge, this is the first study to demonstrate that a hyper activation of these reward-associated areas is associated not only with the development of craving, but also with real decisions in favour of alcoholic drinks.…”
Section: Discussionmentioning
confidence: 76%